Nordic Innovation Monitor 2009 – Short version (Copenhagen : Nordic Council of Ministers, 2009)
At the 26 and 27 of February 2009, the second Nordic Globalization Forum will take place in Iceland. The Forum this year will focus on climate, energy and innovation. The Nordic Innovation Monitor will be presented for the first time ever at the Globalization Forum 2009. The Nordic Innovation Monitor gives an in depth analysis of the innovation performance of the Nordic countries compared with leading countries in the world and the framework conditions that exist in the individual countries. This allows for a fact based policy, and for learning from those countries in the world that shape the best conditions for innovation.